2020
DOI: 10.1088/1361-648x/ab6f89
|View full text |Cite
|
Sign up to set email alerts
|

Helical nanobots as mechanical probes of intra- and extracellular environments

Abstract: Supporting information1. Dynamics of helical nanobots under rotating magnetic fields A helical nanorobot actuated under rotating magnetic field shows different kind of dynamics depending upon the applied field, frequency and the fluid viscosity. This difference in dynamics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…However, motion of helical magnetic nanorobots was successfully explored in Hela, kidney, and endothelial cells environments after incubation and internalization. [ 359 ] This robotic intracellular probe approach was also demonstrated to measure viscosity, [ 360 ] and adhesive forces inside metastatic cancer cells. [ 361 ] Piezoelectric microrobots were also reported as wireless probes for neural stimulation mapping and differentiation of single cell using the piezoelectric effect produced by an external ultrasound field.…”
Section: Diagnosismentioning
confidence: 99%
“…However, motion of helical magnetic nanorobots was successfully explored in Hela, kidney, and endothelial cells environments after incubation and internalization. [ 359 ] This robotic intracellular probe approach was also demonstrated to measure viscosity, [ 360 ] and adhesive forces inside metastatic cancer cells. [ 361 ] Piezoelectric microrobots were also reported as wireless probes for neural stimulation mapping and differentiation of single cell using the piezoelectric effect produced by an external ultrasound field.…”
Section: Diagnosismentioning
confidence: 99%
“…It was observed that at the site of injection of nanorobots many of them got adhered to the glass slide. The presence of local pockets of injected fluids has been reported in a previous literature 69 , where it was shown that within a time scale of approximately 30 minutes, the system gains its structural uniformity.…”
Section: D Culture and Experimental Procedurementioning
confidence: 54%
“…[ 144 ] Magnetic helical nanorobots as mechanical probes realized accurate measurement of cytoplasmic viscosity of HeLa cell. [ 155 ]…”
Section: Versatile Biomedical Applications Of Magnetic Micro/nanorobotsmentioning
confidence: 99%